Better than expected: the gap between self-reported and objective measures of cognitive performance in remitted bipolar disorder - Quinlivan, Esther; Renneberg, Babette; Schreiter, Stefanie; Friedel, Eva; Shmuilovich, Olga; Stamm, Thomas (Frontiers in Psychiatry, 2023)
Background: Studies comparing objective and self-reported cognitive functioning as well as influencing factors in individuals with remitted bipolar disorder are scarce and contradictory.The aim of this study was to compare executive functioning and other objective and selfreported cognitive impairment between 26 individuals with remitted bipolar disorder (15 BD I) and 24 healthy controls using a cross-sectional design. Executive functions were measured by the TAP Go/No-go subtest as well as the Stroop Task. Self-rated functioning was assessed using the Attention Deficit Experience Questionnaire. In addition, possible predictors of self-reported and objective cognitive functioning were examined to perform regression analyses.Results: Individuals with remitted bipolar disorder did not differ significantly in executive functions or other objective cognitive domains from the healthy control group, but showed a significantly lower level of self-reported cognitive functioning and self-esteem. While self-esteem was the strongest predictor in healthy controls for self-reported cognitive functioning, severity of illness and subthreshold depressive mood were the most important predictors in individuals with remitted bipolar disorder.The results once again demonstrate the cognitive heterogeneity in bipolar disorder. In the treatment of cognitive deficits, factors such as subthreshold depressive symptomatology and selfesteem should be focused on in addition to cognitive training in remitted patients.